Association of Vitamin D Metabolites With Embryo Development and Fertilization in Women With and Without PCOS Undergoing Subfertility Treatment - Cunningham, Thomas Keith; Allgar, Victoria; Dargham, Soha R.; Kilpatrick, Eric; Sathyapalan, Thozhukat; Maguiness, Stephen; Mokhtar Rudin, Haira R.; Abdul Ghani, Nour M.; Latiff, Aishah; Atkin, Stephen L. (Frontiers in Endocrinology, 2019)
Objective: The relationship between fertilization rates and 1,25-dihydroxyvitamin D (1,25(OH)2D3), 25-hydroxyvitamin D2 (25(OH)D2), 25-hydroxyvitamin D3 (25(OH)D3), 24,25-dihydroxyvitamin D (24,25(OH)2D3), and 25-hydroxy-3epi-Vitamin D3 (3epi25(OH)D3) concentrations in age and weight matched women with and without PCOS was studied. Methods: Fifty nine non-obese women, 29 with PCOS, and 30 non-PCOS undergoing IVF, matched for age and weight were included. Serum vitamin D metabolites were taken the menstrual cycle prior to commencing controlled ovarian hyperstimulation. Results: Vitamin D metabolites did not differ between PCOS and controls; however, 25(OH)D3 correlated with embryo fertilization rates in PCOS patients alone (p = 0.03). For all subjects, 3epi25(OH)D3 correlated with fertilization rate (p < 0.04) and negatively with HOMA-IR (p < 0.02); 25(OH)D2 correlated with cleavage rate, G3D3 and blastocyst (p < 0.05; p < 0.009; p < 0.002, respectively). 24,25(OH)2D3 correlated with AMH, antral follicle count, eggs retrieved and top quality embryos (G3D3) (p < 0.03; p < 0.003; p < 0.009; p < 0.002, respectively), and negatively with HOMA-IR (p < 0.01). 1,25(OH)2D3 did not correlate with any of the metabolic or embryo parameters. In slim PCOS, 25(OH)D3 correlated with increased fertilization rates in PCOS, but other vitamin D parameters did not differ to matched controls. Conclusion: 3epi25(OH)D3, 25(OH)D2, and 24,25(OH)2D3, but not 1,25(OH)2D3, were associated with embryo parameters suggesting that vitamin D metabolites other than 1,25(OH)2D3 are important in fertility.